HIGIENE SANITASI SERTA PEMERIKSAAN Escherichia coli dan RHODAMIN B PADA MAKANAN JAJANAN DI SEKOLAH DASAR (SD) KELURAHAN TIMBANG DELI KECAMATAN MEDAN AMPLAS TAHUN 2013 - Henny Rifcha Situmorang; Dra. Nurmaini MKM, PhD; Dr. dr. Wirsal Hasan MPH (Lingkungan dan Kesehatan Kerja, 2014)
Hygiene sanitation well as examination of Escherichia coli and Rhodamine B in the street food at Elementary School Village Timbang Deli District Medan Amplas in 2013. Street food sold at Elementary School Village Timbang Deli District Medan Amplas had a lot of varieties, street food vendors vend their merchandise on the roadside and most of it was processed by individual and should fulfill health requirement. This research aimed to know about hygiene sanitation well as the content of Escherichia coli and Rhodamine B in the street food sold at Elementary School Village Timbang Deli District Medan. The design of this research was descriptive which is to see the representation of hygiene sanitation, laboratory test to determine the content of Escherichia coli and Rhodamine B in the street food. The results showed that the street food hygiene sanitation doesn’t fulfill health requirement based on Permenkes RI No. 942/Menkes/SK/VII/2003 which includes, food handlers, equipment used, presentation manner, facilities vendors and there is one person vendors using food ingredients that dosen’t registered in Depkes RI and doesn’t have expiry date. The laboratory test showed that 9 of 10 samples contained Escherichia coli. They were Es Jagung, 3 Air Es, Tahu Bakar, Es Buah, Mie Goreng, Lontong, Telur Dadar Gulung, while one sample which didn’t contain Escherichia coli was Bakso Kuah Kari. It also showed that all the samples didn’t contain Rhodamine B. The samples were 2 saos, Somboi, Kerupuk Berwarna Merah, Tahu Bakar, Es Berwarna Merah, were eligible health based Permenkes RI No. 239/Menkes/PER/V/1985. Based on this result, street food vendors were expected to maintain hygiene sanitation when processing or preparing food. Dinas Kesehatan Kota Medan needs to hold counseling or supervising for street food hygiene sanitation that fulfill the health requirements.Keywords: street food, hygiene sanitation, Escherichia coli, Rhodamine B